Spacecraft adaptive nonlinear attitude tracking with harmonic disturbances and inertia uncertainties - Li, Chuanjiang; Guo, Yanning; Ma, Guangfu; Du, Shaohe (Chinese Control Conference, 2014)
In this paper, an adaptive controller is proposed for spacecraft attitude tracking problem subject to inertia uncertainties and harmonic disturbances. A class of sinusoidal disturbances with known frequencies but unknown amplitudes and phase angles are considered. The proposed controller is composed of a nonlinear proportional-derivative (PD) control part and an adaptive control part. The internal model control is utilized to identify the harmonic disturbances. The nonlinear PD control term is designed to achieve better tracking performance with shorter settling time and smaller/no overshoot. The overall closed-loop tracking error system is shown to be globally asymptotically stable via Lyapunov stability theory. Finally, numerical simulations are carried out to illustrate the effectiveness of the proposed methodology.